2012
DOI: 10.1002/lary.23515
|View full text |Cite
|
Sign up to set email alerts
|

Subglottic injury: A clinically relevant animal model

Abstract: Our model provides a reliable and reproducible technique for acute/subacute injury to the subglottis secondary to intubation, which is consistent with previous histological findings of early changes associated with acquired subglottic stenosis (SGS). Future uses of this model could include the examination of current adjunctive therapies and their effects on limiting progression to SGS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 36 publications
1
33
0
Order By: Relevance
“…The pathogenic mechanism of post intubation SGS has been well established as a progression from mucosal injury to granulation tissue and subsequent scarring fibrosis [11]. Given that by definition idiopathic SGS does not have an identifiable trauma it seems reasonable to theorize that this cascade of scarring results from another initiating inflammatory event.…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenic mechanism of post intubation SGS has been well established as a progression from mucosal injury to granulation tissue and subsequent scarring fibrosis [11]. Given that by definition idiopathic SGS does not have an identifiable trauma it seems reasonable to theorize that this cascade of scarring results from another initiating inflammatory event.…”
Section: Discussionmentioning
confidence: 99%
“…As other studies have suggested, additional contributing factors include microbiome shifts in the larynx and trachea 38 and the ensuing perichondritis after hypoxic injury caused by intubation. 39 Recent discoveries also highlight the potential for a genetic predisposition to laryngotracheal scar formation; one study found an association between a polymorphism in matrix metalloproteinase 1 (MMP1) and the formation of scar after intubation injury. 40 This discovery complements our finding of elevated MMP activity after hypoxic stimulation of normal laryngotracheal fibroblasts, suggesting that genetic predisposition may enhance the effects of hypoxia on the laryngotracheal ECM.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of animal models of subglottic stenosis exist, of which a select cohort are listed here [2832]. However, there are few reports of in vivo OCT of subglottic stenosis models with comparative histologic analysis [24].…”
Section: Discussionmentioning
confidence: 99%